2018
DOI: 10.1021/acsenergylett.8b01257
|View full text |Cite
|
Sign up to set email alerts
|

Lithium–Organic Nanocomposite Suspension for High-Energy-Density Redox Flow Batteries

Abstract: Organic redox-active materials are promising for redox flow batteries (RFBs) owing to their inherent low-cost, vast abundance, and high structure tunability. However, many organic RFBs suffer from low energy density owing to low solubility. We demonstrate a facile lithium−organic nanocomposite suspension (LIONS) by melting solid organic materials into the void of carbon networks in the semisolid posolyte to achieve high-energy-density Li-RFBs. We demonstrate the first organic-based semisolid Li-RFBs using 10-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 53 publications
0
35
0
Order By: Relevance
“…[9][10][11] In particular, recent studies on non-aqueous all-organic RFBs (NORFBs) have demonstrated the great promise for achieving high energy densities in these systems without the concerns associated with water electrolysis, which typically limits the working voltage to a narrow range and thus leads to a rather low energy density in aqueous RFBs. [12][13][14][15][16][17] Despite the great potential of organic RFBs, their practical energy density remains very low. 10 The energy density of ROM-based RFBs is dependent on the following…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] In particular, recent studies on non-aqueous all-organic RFBs (NORFBs) have demonstrated the great promise for achieving high energy densities in these systems without the concerns associated with water electrolysis, which typically limits the working voltage to a narrow range and thus leads to a rather low energy density in aqueous RFBs. [12][13][14][15][16][17] Despite the great potential of organic RFBs, their practical energy density remains very low. 10 The energy density of ROM-based RFBs is dependent on the following…”
Section: Introductionmentioning
confidence: 99%
“…In a GITT test (Figure S4, Supporting Information) that resembles an intermittent charge/discharge test with prolonged reaction time, the utilization can be improved to 82.3% which is slightly lower than the highest reported utilization results . Considering a 82.3% utilization and 41% loading ratio of NVP, and a maximum concentration of mediators (0.3 m for MPTZ and 0.9 m for FL), the half‐cell capacity is estimated to be 137 Ah L −1 (5.1 m , 17 times of 0.3 m of MPTZ) and 81 Ah L −1 (3.1 m , 3 times of 0.9 m of FL) for catholyte and anolyte, respectively, corresponding to a full‐cell energy density of 88 Wh L −1 . A catholyte‐controlled full cell was then constructed to concomitantly demonstrate the operations of both anodic and cathodic SMRT reactions.…”
Section: Resultsmentioning
confidence: 88%
“…Ideally, to realize SMRT reaction in both directions, E E RM O NVP O − should equal to 0. [36] For nonaqueous redox flow batteries, various phenothiazine derivatives have also been reported among which the highest solubility is 0.5 m achieved with N-[2-(2-methoxyethoxy)ethyl]phenothiazine (MEEPT). Apart from molecular engineering and searching for new molecules, altering the solvation environment with different solvents is another effective way in nonaqueous system to manipulate the equilibrium redox potential.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations